Composite material, composite lithium supplement, preparation method and application thereof
By using a composite composed of Ni@Co@M metal aerogel and solid electrolyte to coat lithium oxalate, the problem of lithium resource loss during charging and discharging of lithium-ion batteries is solved, and a lower deliquency potential and higher The charging and discharging specific capacity improves the overall performance of the battery.
Patent Information
- Application Number
- CN202411527001.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-30
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a composite material, a composite lithium supplement, and a preparation method and application thereof. Background Art
[0002] During the charging process of a standard lithium-ion battery, a solid electrolyte interface (SEI) film forms on the surface of the negative electrode. This process consumes the active lithium released from the positive electrode, causing some irreversible loss of lithium resources, which in turn affects the overall performance of the battery, manifesting as a decrease in the battery's initial charging efficiency and discharge capacity. Therefore, improving the discharge capacity of the battery's positive electrode and the lithium ion transport capacity has become a research focus.
[0003] To address this challenge, current research focuses on adding lithium-supplementing additives to cathode materials. These additives are designed to replenish consumed lithium ions without destroying the structure of the cathode material, thereby increasing the battery's discharge capacity. However, existing lithium-supplementing additives face multiple challenges, such as insufficient lithium replenishment, low efficiency, and potential negative impacts on the structural stability of the cathode material. These limitations hinder the widespread application of lithium-supplementing additives in practical battery manufacturing.
[0004] Patent application CN117559013A utilizes a lithium-supplementing agent and a conductive material to form a lithium-supplementing agent composite material. By adding the lithium-supplementing agent composite material to the battery's positive electrode, the positive electrode is replenished with lithium during the battery's charge and discharge processes, effectively increasing the specific discharge capacity of the battery's positive electrode. However, the decomposition byproducts of the lithium-supplementing agent used in this patent during cycling can exacerbate side reactions at the interface between the electrode liquid and the positive electrode, resulting in reduced cycling performance. Summary of the Invention
[0005] In view of this, the technical problem to be solved by the present invention is to provide a composite, a composite lithium supplement, a preparation method and application thereof. The composite lithium supplement is prepared using the composite, and the lithium ion battery finally prepared has a low delithiation potential and a high initial charge and discharge specific capacity.
[0006] The present invention provides a composite material comprising a metal aerogel and a solid electrolyte;
[0007] The metal aerogel is Ni@Co@M metal aerogel, where M is Mo or Fe;
[0008] The solid electrolyte is selected from lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide or lithium lanthanum titanium oxide.
[0009] Preferably, the composite is obtained by sintering a mixture of a solid electrolyte precursor solution and a metal aerogel at high temperature.
[0010] Preferably, the preparation method of the mixture comprises the following steps:
[0011] The solid electrolyte precursor solution is mixed with the metal aerogel and dried to obtain a mixture.
[0012] Preferably, the high temperature sintering includes:
[0013] The mixture is heated to 700-900° C. and kept warm, and then heated to 1000-1200° C. and kept warm;
[0014] The high-temperature sintering is carried out in a protective gas atmosphere.
[0015] Preferably, the heating rate to 700-900°C is 0.5-5°C / min, and the holding time at 700-900°C is 3-6 h;
[0016] The heating rate for reheating to 1000~1200℃ is 1~4℃ / min, and the holding time at 1000~1200℃ is 5~10 h.
[0017] Preferably, the preparation method of the Ni@Co@M metal aerogel comprises the following steps:
[0018] An aqueous solution containing a structure-directing agent and a complexing agent, a cobalt source, a nickel source, an M source, and a reducing agent are mixed, deoxygenated, and then heated and stirred at 40-80°C to form a hydrogel. After drying or solvent replacement, a Ni@Co@M metal aerogel is obtained; the M source is a Mo source or an Fe source.
[0019] Preferably, the structure directing agent comprises at least one of a polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, hexadecyltrimethylammonium bromide and a polyoxyethylene polyoxypropylene ether block copolymer;
[0020] The complexing agent includes at least one of sodium citrate, nitrilotriacetic acid, ethylenediaminetetraacetic acid and adenosine triphosphate;
[0021] The mass ratio of the structure directing agent to the complexing agent is (40-80): (60-120);
[0022] In the aqueous solution containing the structure directing agent and the complexing agent, the mass ratio of the total mass of the structure directing agent and the complexing agent to water is 1:(15-25).
[0023] Preferably, the cobalt source includes at least one of cobalt acetate, cobalt acetylacetonate and cobalt nitrate;
[0024] The nickel source includes nickel acetate and / or nickel nitrate;
[0025] The Mo source includes molybdenum acetate dimer and / or ammonium molybdate;
[0026] The Fe source includes ferric nitrate and / or ferric acetylacetonate;
[0027] The reducing agent includes at least one of dimethylamine borane, sodium borohydride, ascorbic acid and metal organic frameworks (MOFs).
[0028] Preferably, the mass ratio of the structure directing agent, complexing agent, cobalt salt, nickel salt, M source and reducing agent is (40-80): (60-120): (100-150): (100-150): (100-150): (800-1000).
[0029] The present invention also provides a composite lithium supplement comprising:
[0030] lithium oxalate;
[0031] an aerogel coating layer formed on the surface of the lithium oxalate;
[0032] The component of the aerogel coating layer is the composite material described above.
[0033] The present invention also provides a method for preparing the composite lithium supplement agent described above, comprising the following steps:
[0034] A) Grinding the aqueous solution of lithium oxalate to obtain nano-Li2C2O4;
[0035] B) uniformly dispersing the composite and the nano-Li2C2O4 in deionized water, ultrasonically treating, and then performing a hydrothermal reaction to obtain a composite lithium supplement.
[0036] Preferably, in step B), the mass ratio of the composite to the nano-Li2C2O4 is 1:(3-9);
[0037] The power of the ultrasonic treatment is 500~3000 W, and the time is 0.5~5 h;
[0038] The temperature of the hydrothermal reaction is 140-220° C., and the time is 6-24 h.
[0039] The present invention also provides a lithium ion battery, wherein the positive electrode of the lithium ion battery comprises a composite lithium supplement;
[0040] The composite lithium supplement is the composite lithium supplement described above, or is the composite lithium supplement prepared by the preparation method described above.
[0041] The present invention provides a composite comprising a metal aerogel and a solid electrolyte. The metal aerogel is a Ni@Co@M metal aerogel, where M is Mo or Fe. The solid electrolyte is selected from lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, or lithium lanthanum titanate oxide. The composite is used as a component of the aerogel coating and combined with lithium oxalate to form a composite lithium supplement. The present invention first prepares the Ni@Co@M metal aerogel. Then, through high-temperature sintering, a solid electrolyte is synthesized in situ on the Ni@Co@M metal aerogel to form a solid electrolyte catalyst (i.e., the composite). Finally, the solid electrolyte catalyst is hydrothermally coated onto nano-lithium oxalate to form a composite lithium oxalate lithium supplement. This provides a new approach to the application of lithium oxalate lithium supplements.
[0042] Compared with the commonly used lithium supplements such as Li5FeO4 and conventional lithium oxalate sacrificial lithium supplements in the market, the lithium supplement of the present invention uses Ni@Co@M multi-metal aerogel as a substrate for the first time, which can provide a high specific surface area and porous structure, which helps to increase the metal sites of the catalyst. A large number of metal sites have high catalytic activity, which helps to promote the decomposition of lithium oxalate and the release of active lithium, thereby improving the electrochemical performance of the lithium supplement. The solid electrolyte provides an ion transmission channel, increasing the ionic conductivity and electronic conductivity of lithium oxalate. At the same time, after the decomposition of lithium oxalate, the solid electrolyte as a reaction product can improve the interfacial stability between the positive electrode and the electrolyte, reduce interfacial reactions, thereby reducing interfacial impedance and improving the overall performance of the battery. The lithium-ion battery prepared from the composite lithium supplement of the present invention has a low delithiation potential and a high initial charge and discharge specific capacity. DETAILED DESCRIPTION
[0043] The following will clearly and completely describe the technical solutions of the present invention in conjunction with the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0044] The present invention provides a composite (solid electrolyte / Ni@Co@M aerogel), comprising a metal aerogel and a solid electrolyte;
[0045] The metal aerogel is Ni@Co@M metal aerogel, where M is Mo or Fe;
[0046] The solid electrolyte is selected from lithium aluminum titanium phosphate (LATP), lithium lanthanum zirconium oxide (LLZO) or lithium lanthanum titanium oxide (LLTO).
[0047] The composite is obtained by sintering a mixture of a solid electrolyte precursor solution and a metal aerogel at high temperature.
[0048] In certain embodiments of the present invention, the method for preparing the mixture comprises the following steps:
[0049] The solid electrolyte precursor solution is mixed with the Ni@Co@M metal aerogel and dried to obtain a mixture.
[0050] In certain embodiments of the present invention, the method for preparing the Ni@Co@M metal aerogel comprises the following steps:
[0051] An aqueous solution containing a structure-directing agent and a complexing agent, a cobalt source, a nickel source, an M source, and a reducing agent are mixed, deoxygenated, and then heated and stirred at 40-80°C to form a hydrogel. After drying or solvent replacement, a Ni@Co@M metal aerogel is obtained; the M source is a Mo source or an Fe source.
[0052] The structure-directing agent is at least one of a polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123), cetyltrimethylammonium bromide (CTAB), and a polyoxyethylene polyoxypropylene ether block copolymer (F127). The complexing agent is at least one of sodium citrate, nitrilotriacetic acid, ethylenediaminetetraacetic acid, and adenosine triphosphate. The mass ratio of the structure-directing agent to the complexing agent is 40-80:60-120, such as 40:60, 40:120, or 80:120. In the aqueous solution containing the structure-directing agent and the complexing agent, the mass ratio of the total mass of the structure-directing agent and the complexing agent to water is 1:15-25, such as 1:20 or 1:25. The solvent of the aqueous solution containing the structure-directing agent and the complexing agent is deionized water.
[0053] The cobalt source is at least one of cobalt acetate, cobalt acetylacetonate, and cobalt nitrate. The nickel source is nickel acetate and / or nickel nitrate. The Mo source is molybdenum acetate dimer and / or ammonium molybdate. The Fe source is ferric nitrate and / or ferric acetylacetonate. The reducing agent is at least one of dimethylamine borane, sodium borohydride, ascorbic acid, and metal-organic frameworks (MOFs).
[0054] The mass ratio of the structure directing agent, complexing agent, cobalt salt, nickel salt, M source and reducing agent is 40~80:60~120:100~150:100~150:100~150:800~1000, for example, 40:60:100:100:100:800, 40:120:100:125:150:1000, and 80:120:100:125:150:900.
[0055] The deoxygenation method comprises:
[0056] The mixture is evacuated and replaced with an inert gas to remove dissolved oxygen from the mixed solution and protect the prepared sample from oxidation. The inert gas may be Ar.
[0057] The heating and stirring time at 40-80° C. is 8-24 h. Specifically, the heating and stirring temperature is 40° C. or 80° C., and the time is 24 h or 8 h.
[0058] In certain embodiments of the present invention, after the hydrogel is formed, the steps include washing and transferring the hydrogel to an alcohol solution for reflux. Deionized water is used for washing. The reflux temperature is 30°C to 60°C, for example, 30°C, and the reflux time is 12 to 20 hours, for example, 12 hours or 20 hours. Transferring the hydrogel to an alcohol solution for reflux is to remove residues. The alcohol solution may be methanol and / or ethanol. Drying methods include freeze drying, supercritical drying, atmospheric pressure drying, vacuum drying, or microwave drying.
[0059] After obtaining the Ni@Co@M metal aerogel, a solid electrolyte is synthesized in situ on the Ni@Co@M metal aerogel to obtain a composite (ie, solid electrolyte / Ni@Co@M aerogel).
[0060] Specifically, they include:
[0061] The solid electrolyte precursor solution is mixed with the Ni@Co@M metal aerogel, dried, and the mixture is then sintered at a high temperature.
[0062] In certain embodiments of the present invention, the mass ratio of the solid electrolyte precursor solution to the Ni@Co@M metal aerogel is 20-50:1, such as 20:1, 50:1, or 30:1.
[0063] In certain embodiments of the present invention, the solid electrolyte precursor solution is a LATP precursor solution, a LLZO precursor solution, or a LLZTO precursor solution.
[0064] In certain embodiments of the present invention, the LATP precursor solution is prepared by stirring and mixing LiNO3, Al(NO3)3·9H2O, Ti(OC4H9)4, NH4H2PO4, citric acid, and water at 30-70° C. The mass ratio of LiNO3, Al(NO3)3·9H2O, Ti(OC4H9)4, NH4H2PO4, and citric acid is 90-105:150-250:480-620:240-360:960-1200, for example, 90:150:480:240:960, 105:250:620:360:1200, and 95:200:540:300:1080. The present invention has no particular limitation on the amount of water used; it can be used to dissolve the LiNO₃, Al(NO₃)₃·9H₂O, Ti(OC₄H₄)₄, NH₄H₂PO₄, and citric acid. The stirring and mixing temperature is 60°C, 70°C, or 50°C; the rotation speed is 100-400 rpm, such as 100 rpm, 400 rpm, or 150 rpm; and the stirring time is 30-240 minutes, such as 120 minutes, 240 minutes, or 160 minutes. The water is deionized water.
[0065] The drying temperature is 50-80° C. and the drying time is 20-48 h.
[0066] In some embodiments of the present invention, the high temperature sintering includes:
[0067] The mixture is heated to 700-900° C. and kept warm, and then heated to 1000-1200° C. and kept warm;
[0068] The high-temperature sintering is carried out in a protective gas atmosphere.
[0069] In certain embodiments of the present invention, the protective gas is nitrogen.
[0070] Before heating the mixture to 700-900° C., the method further includes: introducing a protective gas at a flow rate of 0.5-2 m³ / h, specifically, the flow rate is 0.5 m³ / h, 2 m³ / h, and 1 m³ / h. The heating and heat preservation are both performed in an atmosphere furnace.
[0071] In certain embodiments of the present invention, the heating rate to 700-900°C is 0.5-5°C / min, such as 0.5°C / min, 5°C / min, or 2.5°C / min. The holding time at 700-900°C is 3-6 hours, such as 6 hours, 3 hours, or 4 hours. Specifically, the heating temperature is 700°C, 900°C, or 800°C.
[0072] In certain embodiments of the present invention, the heating rate for reheating to 1000-1200°C is 1-4°C / min, such as 1°C / min, 4°C / min, or 2°C / min. The holding time at 1000-1200°C is 5-10 hours, such as 10 hours, 5 hours, or 6 hours. Specifically, the reheating is performed at 1000°C, 1200°C, or 1100°C. After the reheating and holding at 1000-1200°C, the process further includes: naturally cooling to room temperature.
[0073] The present invention also provides a composite lithium supplement comprising:
[0074] lithium oxalate;
[0075] an aerogel coating layer formed on the surface of the lithium oxalate;
[0076] The component of the aerogel coating layer is the composite material described above.
[0077] The lithium oxalate is nano lithium oxalate.
[0078] The aerogel coating layer is obtained by in-situ synthesis of solid electrolyte from Ni@Co@M metal aerogel.
[0079] Specifically, the aerogel coating layer is obtained by sintering a mixture of a solid electrolyte precursor solution and a metal aerogel at high temperature.
[0080] In the present invention, an aerogel coating layer (ie, a solid electrolyte / Ni@Co@M aerogel coating layer) is formed on the surface of nano-lithium oxalate by a hydrothermal method.
[0081] The present invention also provides a method for preparing the composite lithium supplement agent described above, comprising the following steps:
[0082] A) Grinding the aqueous solution of lithium oxalate to obtain nano-Li2C2O4;
[0083] B) uniformly dispersing the composite and the nano-Li2C2O4 in deionized water, ultrasonically treating, and then performing a hydrothermal reaction to obtain a composite lithium supplement.
[0084] In step A):
[0085] After grinding the aqueous solution of lithium oxalate, nano-Li2C2O4 is obtained.
[0086] In certain embodiments of the present invention, the solvent in the aqueous lithium oxalate solution is deionized water. The mass ratio of lithium oxalate to deionized water in the aqueous lithium oxalate solution is 1:5 to 10, e.g., 1:10 or 1:5. The grinding is performed in a sand mill at a speed of 500 to 2500 rpm, e.g., 500 rpm or 2500 rpm, and for a time of 2 to 8 hours, e.g., 8 hours or 2 hours.
[0087] In step B):
[0088] The composite (solid electrolyte / Ni@Co@M aerogel) and the nano-Li2C2O4 are uniformly dispersed in deionized water, and after ultrasonic treatment, a hydrothermal reaction is performed to obtain a composite lithium supplement;
[0089] The solid electrolyte / Ni@Co@M aerogel is obtained by sintering a Ni@Co@Mo metal aerogel whose pores are filled with a solid electrolyte precursor at high temperature.
[0090] In certain embodiments of the present invention, the mass ratio of the composite (solid electrolyte / Ni@Co@M aerogel) to the nano-Li2C2O4 is 1:3-9, for example, 1:9, 1:3, or 1:7. The ultrasonic treatment is performed at a power of 500-3000 W, for example, 3000 W or 2500 W, for a duration of 0.5-5 h, for example, 0.5 h or 1 h. The hydrothermal reaction is performed at a temperature of 140-220°C, for example, 140°C, 220°C, or 200°C, for a duration of 6-24 h, for example, 24 h, 6 h, or 8 h. The hydrothermal reaction is conducted in a polytetrafluoroethylene-lined pressure reactor.
[0091] In the composite lithium supplement obtained by the present invention, the solid electrolyte / Ni@Co@M aerogel coats nano-lithium oxalate.
[0092] The present invention also provides a lithium ion battery, wherein the positive electrode of the lithium ion battery comprises a composite lithium supplement; the composite lithium supplement is the composite lithium supplement described above, or a composite lithium supplement prepared by the preparation method described above.
[0093] The lithium-ion battery can be a button cell or a soft pack cell.
[0094] When the lithium-ion battery is a button battery:
[0095] The positive electrode of the lithium-ion battery is prepared by coating a positive electrode slurry including a positive electrode active material, a conductive agent, a binder and a solvent on a positive electrode current collector; the positive electrode active material is the composite lithium supplement agent described above, or the composite lithium supplement agent prepared by the preparation method described above.
[0096] The conductive agent is conductive carbon black (SP). The binder is polyvinylidene fluoride (PVDF). The solvent is N-methylpyrrolidone (NMP). The positive electrode current collector is aluminum foil.
[0097] In the positive electrode slurry, the mass ratio of the positive electrode active material, the conductive agent, and the binder is 84-87:8-12:3-7, such as 85:10:5. The solid content of the positive electrode slurry is 20%-35%, such as 25%.
[0098] In certain embodiments of the present invention, the method for preparing the positive electrode of the lithium ion battery comprises the following steps:
[0099] After the positive electrode active material, conductive agent, binder and solvent are mixed evenly, the obtained mixed slurry is coated on the positive electrode current collector, dried, rolled and punched to obtain the positive electrode sheet.
[0100] The coating thickness is 100-250 μm, for example 250 μm. The positive electrode current collector is aluminum foil.
[0101] The drying temperature is 100-140° C. and the drying time is 10-14 h.
[0102] When the lithium-ion battery is a button cell, the negative electrode is a lithium sheet; the separator is a polypropylene porous membrane, specifically Celgard 2400 polypropylene porous membrane; the electrolyte is a 1 mol / L LiPF6 solution, and the solvent is ethylene carbonate (EC) and dimethyl carbonate (DMC), with a volume ratio of 1:1. The button cell is assembled in an argon-filled glove box, where the water and oxygen content is controlled to be less than 0.01 ppm. The cell is then pressurized and sealed using a sealing machine to produce the button cell.
[0103] When the lithium-ion battery is a soft-pack battery:
[0104] The positive electrode of the lithium-ion battery is prepared by coating a positive electrode slurry including a positive electrode active material, a binder, a conductive agent, a lithium supplement agent and a solvent on the surface of the positive electrode current collector; the lithium supplement agent is the composite lithium supplement agent described above, or the composite lithium supplement agent prepared by the preparation method described above.
[0105] The positive electrode active material is a single crystal high nickel ternary material or lithium iron phosphate. The single crystal high nickel ternary material is LiNi 0.92 Co 0.055 Mn 0.25 The binder is a PVDF NMP solution with a mass concentration of 1% to 2%; or the binder is PVDF. The conductive agent is conductive carbon black (SP). The positive electrode current collector is aluminum foil with a thickness of 20 μm.
[0106] The mass ratio of the single crystal high nickel ternary material, the binder, the conductive agent and the lithium supplement agent is 94:3:1.5:1.5. The solid content of the positive electrode slurry is 40% to 60%, for example, 50%.
[0107] In certain embodiments of the present invention, the negative electrode of the lithium-ion battery is a graphite negative electrode. Alternatively, the negative electrode of the lithium-ion battery is prepared by coating the surface of the negative electrode current collector with a negative electrode slurry comprising silicon-carbon negative electrode 1800 (Cruder), conductive agent Super P, thickener (a deionized aqueous solution of sodium carboxymethyl cellulose CMC), binder (a deionized aqueous solution of styrene-butadiene rubber SBR), deionized aqueous solution of polyacrylic acid PAA, and deionized aqueous solution of single-walled carbon nanotubes CNT.
[0108] In certain embodiments of the present invention, the method for preparing the positive electrode of the lithium ion battery comprises the following steps:
[0109] After uniformly mixing the single crystal high nickel ternary material, the binder, the conductive agent, the lithium supplement agent and the solvent, the obtained mixed slurry is coated on the surface of the positive electrode current collector and dried to obtain the positive electrode sheet.
[0110] The coating thickness on a single surface is 100-250 μm, for example, 246 μm. The coating speed is 0.5-1.5 m / min, for example, 1 m / min. The coating on the surface of the positive electrode current collector may be applied on both sides of the positive electrode current collector. The drying temperature is 140-150°C.
[0111] The positive electrode sheet is rolled, the tabs are welded, and the sheet is paired with a graphite negative electrode to prepare a soft-pack battery.
[0112] Alternatively, the positive electrode sheet and the negative electrode sheet are rolled separately, and the tabs are welded to prepare a soft-pack battery; the negative electrode sheet is prepared by uniformly coating a negative electrode slurry including a silicon-carbon composite material, a conductive agent, a thickener, a binder, a polyacrylic acid solution, and a single-walled carbon nanotube solution on a negative electrode collector (copper foil).
[0113] The design voltage of the soft-pack battery is 3~4.25 V and the design capacity is 2.5 Ah.
[0114] The present invention directly prepares a solid-state electrolyte-filled Ni@Co@M metal aerogel catalyst (composite). This catalyst provides a large number of active sites and specific surface area, helping to improve the efficiency of the catalytic reaction and promote the decomposition of lithium oxalate. The conductive properties of the metal aerogel also help improve the battery's electron transport efficiency, thereby enhancing its overall performance. Furthermore, the inclusion of a solid-state electrolyte enhances the structural integrity of the metal aerogel, making it more resistant to mechanical stress during battery cycling, which helps ensure the catalyst's structural stability.
[0115] The present invention coats the surface of nano-lithium oxalate with a solid electrolyte / Ni@Co@M aerogel to form a composite lithium oxalate lithium supplement. The large number of active sites and specific surface area of the catalyst can reduce the decomposition potential of lithium oxalate, allowing the lithium supplement to quickly decompose at a voltage of 4V, replenishing a large amount of active lithium for the battery system. At the same time, after the decomposition of lithium oxalate, the remaining reaction product is a Ni@Co@Mo metal aerogel filled with a solid electrolyte. This reaction product has both the additional ion channels of the solid electrolyte and the high electronic conductivity of the metal aerogel, which can greatly improve the ionic conductivity and electronic conductivity inside the battery, reduce the internal resistance of the battery system, reduce the heat loss of the battery during the charge and discharge process, help reduce the increase in battery temperature, thereby reducing the rate of battery aging and extending the service life of the battery.
[0116] The present invention has no particular limitation on the sources of the raw materials used above, and they can be generally commercially available.
[0117] To further illustrate the present invention, the composite, composite lithium supplement, preparation method and application thereof provided by the present invention are described in detail below with reference to the examples, but they should not be construed as limiting the scope of protection of the present invention.
[0118] Example 1
[0119] 1) Preparation of Ni@Co@Mo metal aerogel:
[0120] In a flask, 40g of P123 and 60g of sodium citrate were completely dissolved in deionized water, with the mass ratio of the total mass of P123 and sodium citrate to the deionized water being 1:20. Then, 100g of cobalt acetate, 100g of nickel acetate, 100g of molybdenum acetate dimer, and 800g of dimethylamine borane were added in sequence. The flask containing the above solution was evacuated and replaced with inert gas Ar to remove dissolved oxygen in the solution and protect the prepared sample from oxidation. Afterwards, the solution was heated and stirred at 40°C for 24h to form a hydrogel. The resulting hydrogel was washed with deionized water, transferred to ethanol, and refluxed at 30°C for 12h to remove residues. Finally, the Ni@Co@Mo metal aerogel was obtained by freeze drying.
[0121] 2) Preparation of Ni@Co@Mo aerogel (mixture) with LATP precursor in the pores:
[0122] 90 g of LiNO3, 150 g of Al(NO3)3·9H2O, 480 g of Ti(OC4H9)4, 240 g of NH4H2PO4 and 960 g of citric acid were weighed and dissolved in 5 L of deionized water. The mixture was stirred at 60 °C and 100 rpm for 120 min to obtain a uniformly mixed LATP precursor solution. The LATP precursor solution was poured into the Ni@Co@Mo aerogel (the mass ratio of the LATP precursor solution to the Ni@Co@Mo aerogel was 20:1) to fill the pores of the Ni@Co@Mo aerogel with the LATP precursor. The mixture was dried at 50 °C for 48 h to obtain a Ni@Co@Mo metal aerogel with the pores filled with the LATP precursor.
[0123] 3) High temperature sintering to obtain LATP / Ni@Co@Mo aerogel (composite):
[0124] The Ni@Co@Mo metal aerogel with LATP precursor in its pores was placed in an atmosphere furnace, nitrogen was introduced at a flow rate of 0.5 m³ / h, the temperature was increased to 700°C at a heating rate of 0.5°C / min, kept warm for 6 h, then increased to 1000°C at a heating rate of 1°C / min, kept warm for 10 h, and naturally cooled to room temperature to obtain LATP / Ni@Co@Mo aerogel.
[0125] 4) Preparation of composite lithium supplement:
[0126] Lithium oxalate was uniformly dispersed in deionized water at a mass ratio of 1:10, then transferred to a sand mill and ground at 500 rpm for 8 hours to produce nano-Li2C2O4. The LATP / Ni@Co@Mo aerogel and nano-Li2C2O4 were uniformly dispersed in deionized water at a mass ratio of 1:9 and sonicated at 3000 W for 0.5 hours. The mixed solution was then transferred to a polytetrafluoroethylene-lined pressure reactor and hydrothermally reacted at 140°C for 24 hours to produce a composite lithium supplement consisting of LATP / Ni@Co@Mo aerogel-coated nano-lithium oxalate.
[0127] Comparative Example 1
[0128] The difference from Example 1 is that: Steps 2) and 3) are not included;
[0129] In step 4):
[0130] Lithium oxalate was uniformly dispersed in deionized water at a mass ratio of 1:10, then transferred to a sand mill and ground at 500 rpm for 8 hours to produce nano-Li2C2O4. The Ni@Co@Mo metal aerogel and nano-Li2C2O4 were uniformly dispersed in deionized water at a mass ratio of 1:9 and sonicated at 3000 W for 0.5 hours. The mixed solution was then transferred to a polytetrafluoroethylene-lined pressure reactor and hydrothermally reacted at 140°C for 24 hours to produce a composite lithium supplement consisting of Ni@Co@Mo aerogel-coated nano-lithium oxalate.
[0131] Comparative Example 2
[0132] The difference from Example 1 is that the LATP / Ni@Co@Mo aerogel-coated lithium oxalate is replaced by graphene oxide sheets and Co3O4 quantum dots-coated lithium oxalate:
[0133] The lithium supplement additive includes lithium oxalate, Co3O4 quantum dots, and graphene oxide sheets. The Co3O4 quantum dots are attached to part of the outer surface of the lithium oxalate, and the graphene oxide sheets coat the outer surfaces of the Co3O4 quantum dots and lithium oxalate. The particle size of the lithium oxalate is 100nm, and the particle size of the Co3O4 quantum dots is 3nm. The graphene oxide sheets are connected by hydrogen bonds to form a three-dimensional conductive network. The graphene oxide sheets have a porous structure. The mass ratio of lithium oxalate, Co3O4 quantum dots, and graphene oxide is 80:10:10.
[0134] Example 2
[0135] 1) Preparation of Ni@Co@Fe metal aerogel:
[0136] In a flask, 40g of CTAB and 120g of nitrilotriacetic acid were completely dissolved in deionized water, with the mass ratio of the total mass of CTAB and nitrilotriacetic acid to the deionized water being 1:25. Then, 100g of cobalt nitrate, 125g of ferric nitrate, 150g of nickel acetylacetonate, and 1000g of sodium borohydride were added in sequence. The flask containing the above solution was then evacuated and replaced with inert gas Ar to remove dissolved oxygen in the solution and protect the prepared sample from oxidation. Afterwards, it was stirred at 80°C for 8h to form a hydrogel. The obtained hydrogel was washed with deionized water and transferred to methanol, which was refluxed at 30°C for 20h to remove the residue. Finally, the Ni@Co@Fe metal aerogel was obtained by freeze drying.
[0137] 2) Preparation of Ni@Co@Fe aerogel with LATP precursor in the pores:
[0138] 105 g of LiNO3, 250 g of Al(NO3)3·9H2O, 620 g of Ti(OC4H9)4, 360 g of NH4H2PO4 and 1200 g of citric acid were weighed and dissolved in 6 L of deionized water. The mixture was stirred at 70 °C and 400 rpm for 240 min to obtain a uniformly mixed LATP precursor solution. The LATP precursor solution was poured into the Ni@Co@Fe aerogel (the mass ratio of the LATP precursor solution to the Ni@Co@Fe aerogel was 50:1) to fill the pores of the Ni@Co@Fe aerogel with the LATP precursor. The mixture was dried at 80 °C for 20 h to obtain a Ni@Co@Fe metal aerogel with the pores filled with the LATP precursor.
[0139] 3) High temperature sintering to obtain LATP / Ni@Co@Fe aerogel:
[0140] The Ni@Co@Fe metal aerogel with LATP precursor in its pores was placed in an atmosphere furnace, nitrogen was introduced at a flow rate of 2 m³ / h, the temperature was increased to 900°C at a heating rate of 5°C / min, kept warm for 3 h, then increased to 1200°C at a heating rate of 4°C / min, kept warm for 5 h, and naturally cooled to room temperature to obtain LATP / Ni@Co@Fe aerogel.
[0141] 4) Preparation of composite lithium supplement:
[0142] Lithium oxalate was uniformly dispersed in deionized water at a mass ratio of 1:5, then transferred to a sand mill and ground at 2500 rpm for 2 hours to produce nano-Li2C2O4. The LATP / Ni@Co@Fe aerogel and nano-Li2C2O4 were uniformly dispersed in deionized water at a mass ratio of 1:3 and sonicated at 3000 W for 0.5 hours. The mixed solution was then transferred to a polytetrafluoroethylene-lined pressure reactor and hydrothermally reacted at 220°C for 6 hours to produce a composite lithium supplement consisting of LATP / Ni@Co@Fe aerogel-coated nano-lithium oxalate.
[0143] Comparative Example 3
[0144] The difference from Example 2 is that the LATP / Ni@Co@Fe aerogel catalyst coating is replaced by LATP coating:
[0145] 1) Preparation of LATP precursor:
[0146] Weigh 105 g of LiNO3, 250 g of Al(NO3)3·9H2O, 620 g of Ti(OC4H9)4, 360 g of NH4H2PO4 and 1200 g of citric acid, then dissolve them in 6 L of deionized water, stir at 70 ° C and 400 rpm for 240 min to obtain a uniformly mixed LATP precursor solution, and dry it at 80 ° C for 20 h to obtain LATP precursor.
[0147] 2) High temperature sintering to obtain LATP aerogel:
[0148] The LATP precursor was placed in an atmosphere furnace, heated to 900°C at a heating rate of 5°C / min, kept warm for 3 hours, then heated to 1200°C at a heating rate of 4°C / min, kept warm for 5 hours, and naturally cooled to room temperature to obtain LATP aerogel.
[0149] 3) Preparation of composite lithium supplement:
[0150] Lithium oxalate was uniformly dispersed in deionized water at a mass ratio of 1:5, then transferred to a sand mill and ground at 2500 rpm for 2 hours to produce nano-Li2C2O4. The LATP aerogel and nano-Li2C2O4 were uniformly dispersed in deionized water at a mass ratio of 1:3 and sonicated at 3000 W for 0.5 hours. The mixed solution was then transferred to a polytetrafluoroethylene-lined pressure reactor and hydrothermally reacted at 220°C for 6 hours to produce a composite lithium supplement consisting of LATP aerogel-encapsulated nano-lithium oxalate.
[0151] Example 3
[0152] 1) Preparation of Ni@Co@Mo metal aerogel:
[0153] In a flask, 80g of F127 and 120g of adenosine triphosphate were completely dissolved in deionized water, with the total mass of F127 and adenosine triphosphate to the deionized water in a mass ratio of 1:20. Then, 100g of cobalt acetylacetonate, 125g of nickel acetate, 150g of ammonium molybdate, and 900g of ascorbic acid were added in sequence. The flask containing the above solution was evacuated and replaced with inert gas Ar to remove dissolved oxygen in the solution and protect the prepared sample from oxidation. Afterwards, the mixture was heated and stirred at 80°C for 8h to form a hydrogel. The resulting hydrogel was washed with deionized water and transferred to ethanol, which was refluxed at 30°C for 20h to remove residues. Finally, the Ni@Co@Mo metal aerogel was obtained by freeze drying.
[0154] 2) Preparation of Ni@Co@Mo aerogel with LATP precursor in the pores:
[0155] 95 g of LiNO3, 200 g of Al(NO3)3·9H2O, 540 g of Ti(OC4H9)4, 300 g of NH4H2PO4 and 1080 g of citric acid were weighed and dissolved in 5 L of deionized water. The mixture was stirred at 50 °C and 150 rpm for 160 min to obtain a uniformly mixed LATP precursor solution. The LATP precursor solution was poured into the Ni@Co@Mo aerogel (the mass ratio of the LATP precursor solution to the Ni@Co@Mo aerogel was 30:1) to fill the pores of the Ni@Co@Mo aerogel with the LATP precursor. The mixture was dried at 60 °C for 36 h to obtain a Ni@Co@Mo metal aerogel with the pores filled with the LATP precursor.
[0156] 3) High temperature sintering to obtain LATP / Ni@Co@Mo aerogel:
[0157] The Ni@Co@Mo metal aerogel with LATP precursor in its pores was placed in an atmosphere furnace, nitrogen was introduced at a flow rate of 1 m³ / h, the temperature was increased to 800°C at a heating rate of 2.5°C / min, kept warm for 4 h, then increased to 1100°C at a heating rate of 2°C / min, kept warm for 6 h, and naturally cooled to room temperature to obtain LATP / Ni@Co@Mo aerogel.
[0158] 4) Preparation of composite lithium supplement:
[0159] Lithium oxalate was uniformly dispersed in deionized water at a mass ratio of 1:7, then transferred to a sand mill and ground at 2000 rpm for 3 hours to produce nano-Li2C2O4. The LATP / Ni@Co@Mo aerogel and nano-Li2C2O4 were uniformly dispersed in deionized water at a mass ratio of 1:5 and sonicated at 2500 W for 1 hour. The mixed solution was then transferred to a polytetrafluoroethylene-lined pressure reactor and hydrothermally reacted at 200°C for 8 hours to produce a composite lithium supplement consisting of LATP / Ni@Co@Mo aerogel-coated nano-lithium oxalate.
[0160] Comparative Example 4
[0161] The difference from Example 3 is:
[0162] The LATP / Ni@Co@Mo aerogel coating is replaced with LATP / Ni@Co@Mo ordinary catalyst coating:
[0163] 1) Preparation of conventional catalyst (Ni@Co@Mo catalyst):
[0164] 100g of Ketjen Black, 100g of cobalt acetylacetonate, 125g of nickel acetate, 150g of ammonium molybdate, and 900g of ascorbic acid were completely dissolved in deionized water at a mass ratio of 1:20. The resulting solution was heated and stirred at 80°C for 8 hours and then dried in a 100°C oven for 24 hours. The mixture was then placed in an N2 atmosphere furnace and heated to 950°C at a rate of 2°C / min. The temperature was maintained for 3 hours and then cooled naturally to room temperature to obtain the Ni@Co@Mo catalyst.
[0165] 2) Preparation of a mixture of LATP precursor and Ni@Co@Mo catalyst:
[0166] 95 g of LiNO3, 200 g of Al(NO3)3·9H2O, 540 g of Ti(OC4H9)4, 300 g of NH4H2PO4 and 1080 g of citric acid were weighed and dissolved in 5 L of deionized water. The mixture was stirred at 50°C and 150 rpm for 160 min to obtain a uniformly mixed LATP precursor solution. The Ni@Co@Mo catalyst was added to the LATP precursor solution (the mass ratio of the LATP precursor solution to the Ni@Co@Mo catalyst was 30:1), stirred at 60°C and 2000 rpm for 30 min, and then dried at 80°C for 36 h to obtain a mixture of the LATP precursor and the Ni@Co@Mo catalyst.
[0167] 3) High temperature sintering to obtain LATP / Ni@Co@Mo catalyst:
[0168] A mixture of LATP precursor and Ni@Co@Mo catalyst was placed in an atmosphere furnace, nitrogen was introduced at a flow rate of 1 m³ / h, and the temperature was increased to 800°C at a heating rate of 2.5°C / min, kept at that temperature for 4 h, and then increased to 1100°C at a heating rate of 2°C / min, kept at that temperature for 6 h, and naturally cooled to room temperature to obtain LATP / Ni@Co@Mo catalyst.
[0169] 4) Preparation of composite lithium supplement:
[0170] Lithium oxalate was uniformly dispersed in deionized water at a mass ratio of 1:7, then transferred to a sand mill and ground at 2000 rpm for 3 hours to produce nano-Li2C2O4. The LATP / Ni@Co@Mo catalyst and nano-Li2C2O4 were uniformly dispersed in deionized water at a mass ratio of 1:5 and sonicated at 2500 W for 1 hour. The mixed solution was then transferred to a polytetrafluoroethylene-lined pressure reactor and hydrothermally reacted at 200°C for 8 hours to produce a composite lithium supplement containing nano-lithium oxalate coated with the LATP / Ni@Co@Mo catalyst.
[0171] Example 4
[0172] 1) Preparation of Ni@Co@Mo metal aerogel:
[0173] Same as step 1 of Example 1).
[0174] 2) Preparation of Ni@Co@Mo aerogel with LLZO precursor filled in the pores:
[0175] 480 g of LiNO3, 1300 g of La(NO3)3·6H2O, 650 g of ZrC2H3O2)4 and 800 g of citric acid were weighed and dissolved in 5 L of deionized water. The mixture was stirred at 45 °C and 250 rpm for 120 min to obtain a uniformly mixed LLZO precursor solution. The LLZO precursor solution was poured into the Ni@Co@Mo aerogel (the mass ratio of the LLZO precursor solution to the Ni@Co@Mo aerogel was 20:1) to fill the pores of the Ni@Co@Mo aerogel with the LLZO precursor solution. The mixture was dried at 50 °C for 36 h to obtain a Ni@Co@Mo metal aerogel with the pores filled with LLZO precursor.
[0176] 3) High temperature sintering to obtain LLZO / Ni@Co@Mo aerogel:
[0177] The Ni@Co@Mo metal aerogel with LLZO precursor in its pores was placed in an atmosphere furnace, nitrogen was introduced at a flow rate of 1 m³ / h, the temperature was raised to 950°C at a heating rate of 0.5°C / min, and the temperature was kept at that temperature for 12 hours. After naturally cooling to room temperature, LLZO / Ni@Co@Mo aerogel was obtained.
[0178] 4) Preparation of composite lithium supplement:
[0179] Lithium oxalate was uniformly dispersed in deionized water at a mass ratio of 1:10, then transferred to a sand mill and ground at 500 rpm for 8 hours to produce nano-Li2C2O4. The LLZO / Ni@Co@Mo aerogel and nano-Li2C2O4 were uniformly dispersed in deionized water at a mass ratio of 1:9 and sonicated at 3000 W for 0.5 hours. The mixed solution was then transferred to a polytetrafluoroethylene-lined pressure reactor and hydrothermally reacted at 140°C for 24 hours to produce a composite lithium supplement consisting of LLZO / Ni@Co@Mo aerogel-coated nano-lithium oxalate.
[0180] Example 5
[0181] 1) Preparation of Ni@Co@Mo metal aerogel:
[0182] Same as step 1) in Example 3).
[0183] 2) Preparation of Ni@Co@Mo aerogel with pores filled with LLTO precursor:
[0184] 25 g of LiNO3, 240 g of La(NO3)3·6H2O, 1000 g of Ti(OC4H9)4 and 640 g of citric acid were weighed and dissolved in 5 L of deionized water. The mixture was stirred at 60°C and 200 rpm for 90 min to obtain a uniformly mixed LLTO precursor solution. The LLTO precursor solution was poured into the Ni@Co@Mo aerogel (the mass ratio of the LLTO precursor solution to the Ni@Co@Mo aerogel was 15:1) to fill the pores of the Ni@Co@Mo aerogel with the LLTO precursor. The mixture was dried at 60°C for 36 h to obtain a Ni@Co@Mo metal aerogel with the pores filled with the LLTO precursor.
[0185] 3) High temperature sintering to obtain LLTO / Ni@Co@Mo aerogel:
[0186] The Ni@Co@Mo metal aerogel with pores filled with LLTO precursor was placed in an atmosphere furnace, nitrogen was introduced at a flow rate of 0.5 m³ / h, the temperature was increased to 600°C at a heating rate of 0.5°C / min, kept warm for 5 h, then increased to 1100°C at a heating rate of 1°C / min, kept warm for 12 h, and naturally cooled to room temperature to obtain LLTO / Ni@Co@Mo aerogel.
[0187] 4) Preparation of composite lithium supplement:
[0188] Lithium oxalate was uniformly dispersed in deionized water at a mass ratio of 1:10, then transferred to a sand mill and ground at 500 rpm for 8 hours to produce nano-Li2C2O4. The LLTO / Ni@Co@Mo aerogel and nano-Li2C2O4 were uniformly dispersed in deionized water at a mass ratio of 1:9 and sonicated at 3000 W for 0.5 hours. The mixed solution was then transferred to a polytetrafluoroethylene-lined pressure reactor and hydrothermally reacted at 140°C for 24 hours to produce a composite lithium supplement consisting of LLTO / Ni@Co@Mo aerogel-coated nano-lithium oxalate.
[0189] Preparation of button cells:
[0190] The composite lithium supplement prepared in Examples 1 to 5 and Comparative Examples 1 to 4 was used as the positive electrode active material, the conductive agent SP, and the binder PVDF were mixed in a mass ratio of 85:10:5, and then mixed with the solvent N-methylpyrrolidone (NMP). The resulting mixed slurry (solid content of 25%) was coated (coating thickness of 250 μm) on aluminum foil, and then placed in a 120°C forced air oven to dry for 12 hours. After roller pressing and punching, a positive electrode sheet was prepared; a metal lithium sheet was used as the negative electrode, a Celgard 2400 polypropylene porous membrane was used as the separator, and a 1 mol / L LiPF6 solution (the solvent was ethylene carbonate (EC) and dimethyl carbonate (DMC), the volume ratio was 1:1) as the electrolyte; the reaction was carried out in an argon-filled glove box, the water oxygen value in the glove box was controlled to be less than 0.01 ppm, and the battery was pressurized and sealed with a sealing machine to obtain a button battery.
[0191] The button cell was subjected to electrochemical performance testing to test the delithiation potential and initial charge and discharge specific capacity of the lithium supplement material. The reduction in the delithiation potential of the lithium supplement material can effectively alleviate the interfacial side reactions between the positive electrode material and the electrolyte at high desorption potentials. The initial charge and discharge specific capacity also reflects the amount of active lithium provided by the lithium supplement material in the battery system. The battery test was carried out at a constant temperature of 25°C, and the charge and discharge mode was: 0.1C constant current charging and 0.1C constant current discharging. The test results are shown in Table 1.
[0192] Table 1 Electrochemical performance data of button battery
[0193]
[0194] Under the same battery system, the delithiation potential of Battery No. 1 is significantly lower than that of Battery No. 6, indicating that the metal aerogel catalyst filled with the LATP solid electrolyte significantly reduces the delithiation potential of lithium oxalate. The large number of active sites and high specific surface area enhance the catalytic effect and accelerate the catalytic reaction. Compared with Battery No. 9, the lithium oxalate supplement coated with LATP / Ni@Co@Mo aerogel in Battery Nos. 3-5 provides more active lithium, compensating for the negative impact of capacity loss caused by the loss of active lithium due to SEI film formation. Compared with Battery No. 7, the lithium oxalate coated with LATP / Ni@Co@Mo aerogel in Battery No. 1 exhibits better ionic conductivity, reduces the energy barrier for lithium ion insertion and deinsertion, and has a lower delithiation potential and higher initial discharge specific capacity. Compared with the No. 8 battery, the No. 2 battery uses lithium oxalate coated with LATP / Ni@Co@Mo aerogel. Ni@Co@Mo aerogel has more metal catalytic sites and a larger specific surface area, which can greatly improve the conductivity of lithium oxalate, reduce the decomposition energy barrier, and have a lower separation potential.
[0195] Preparation of soft pack batteries:
[0196] Using single crystal morphology LiNi 0.92 Co 0.055 Mn 0.25 O2, a PVDF solution with a mass concentration of 1.5% (the solvent is NMP), a conductive agent Super P, and a composite lithium replenisher (the composite lithium replenishers prepared in Examples 1 to 5 and Comparative Examples 1 to 4, respectively) were mixed in a mass ratio of 94:3:1.5:1.5, and NMP was added to obtain a positive electrode slurry with a solid content of 50%. The obtained positive electrode slurry was coated (coating speed of 1 m / min, single-side coating thickness of 246 μm) on both sides of a 20 μm aluminum foil and dried at 145°C to obtain a positive electrode sheet.
[0197] The negative electrode material, silicon-carbon anode 1800 (Cruder), conductive agent Super P, thickener (a deionized aqueous solution of sodium carboxymethyl cellulose (CMC) at a mass concentration of 1.5%), binder (a deionized aqueous solution of styrene-butadiene rubber (SBR) at a mass concentration of 48%), polyacrylic acid (PAA) at a mass concentration of 6%), and single-walled carbon nanotube (CNT) at a mass concentration of 0.4%) were mixed in a mass ratio of 95:0.9:1:1:2:0.1. After mixing, deionized water was added to control the theoretical solid content to 35%. The mixture was homogenized using a vacuum defoamer to obtain a negative electrode slurry. The negative electrode slurry was evenly coated on a 17 μm thick copper foil. After drying, roller pressing, and cutting, 52 mm × 72 mm negative electrode sheets were obtained. The N / P ratio of the positive and negative electrodes was 1.1.
[0198] The positive electrode sheet and the negative electrode sheet are respectively roll-pressed and the tabs are welded to prepare a soft-pack battery.
[0199] The soft-pack battery was subjected to an electrochemical performance test. The design voltage of the soft-pack battery was 3-4.25 V, and the design capacity was 2.5 Ah.
[0200] Test standard: The soft-pack batteries were subjected to room temperature cycle performance tests, and the results are shown in Table 2.
[0201] Battery room temperature cycle performance test:
[0202] The prepared soft-pack battery was placed in a constant temperature room at an ambient temperature of 25°C, charged at a constant current of 1C to a voltage of 4.25V, then charged at a constant voltage of 4.25V to a current of 0.05C, and then discharged at a constant current of 1C to a voltage of 3.0V. The cycle was repeated for 2000 cycles, and the capacity retention rate was recorded. The capacity retention rate (%) of the nth cycle = (discharge capacity of the nth cycle / discharge capacity of the first cycle) × 100%.
[0203] Table 2 Electrochemical performance data of soft pack batteries
[0204]
[0205] As shown in Table 2, under the same battery system, the average room temperature 1C capacity of batteries 10-14 was greater than 2.49 Ah. After 2000 cycles, batteries 10-14 exhibited excellent cycling stability, with 2000-cycle retention rates exceeding 96.3%. This is because as cycling progresses, the SEI on the surfaces of the positive and negative electrode materials expands in volume, and interfacial side reactions between the electrolyte and the positive and negative electrode surfaces occur, causing destruction and reconstruction. This process reshapes the SEI, resulting in the loss of some active lithium. The use of a composite lithium oxalate lithium supplement provides a large amount of active lithium, contributing to the high 2000-cycle retention rate.
[0206] Compared to the AA15 battery, the AA12 battery exhibits significantly higher 1C capacity and 2000-cycle retention. This is due to the use of LATP solid electrolyte coated lithium oxalate. After lithium oxalate decomposes, the LATP solid electrolyte provides a good ion channel, significantly reducing the energy barrier for lithium ion insertion and deintercalation, thereby reducing internal energy loss. Compared to the AA17-18 batteries, the AA10 battery exhibits a higher 1C capacity and excellent 2000-cycle retention. This is because the lithium oxalate used in the AA10 battery has a delithiation potential below 4.2V, while the lithium oxalate used in the AA17-18 batteries decomposes easily at 4.2V and is unable to release active lithium. This demonstrates that the innovative LATP / Ni@Co@Mo aerogel coating technology not only improves the structural stability of lithium oxalate but also promotes its decomposition and release of active lithium during the battery's charge and discharge processes. The addition of LATP enhances the material's ionic conductivity, while the multi-metal synergistic effect of Ni@Co@Mo optimizes the electrochemical reaction kinetics, further reducing the delithiation potential and enabling smoother release of active lithium.
[0207] The above embodiments are intended only to facilitate understanding of the methods and core concepts of the present invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention is not limited to the embodiments shown herein, but is intended to be construed in the widest manner consistent with the principles and novel features disclosed herein.
Claims
1. A composite lithium supplement, characterized in that: include: Lithium oxalate; An aerogel coating layer formed on the surface of the lithium oxalate; The component of the aerogel coating layer is a composite; The composite comprises a metal aerogel and a solid electrolyte; The metal aerogel is Ni@Co@M metal aerogel, where M is Mo or Fe; The solid electrolyte is selected from lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide or lithium lanthanum titanium oxide.
2. The composite lithium supplement according to claim 1, characterized in that: The composite is obtained by sintering a mixture of a solid electrolyte precursor solution and a metal aerogel at high temperature.
3. The composite lithium supplement according to claim 2, characterized in that: The preparation method of the mixture comprises the following steps: The solid electrolyte precursor solution is mixed with the metal aerogel and dried to obtain a mixture.
4. The composite lithium supplement according to claim 2, characterized in that: The high temperature sintering comprises: The mixture is heated to 700-900° C. and kept warm, and then heated to 1000-1200° C. and kept warm; The high-temperature sintering is performed under a protective gas atmosphere.
5. The composite lithium supplement according to claim 4, characterized in that: The heating rate to 700-900°C is 0.5-5°C / min, and the holding time at 700-900°C is 3-6 h; The heating rate for reheating to 1000~1200℃ is 1~4℃ / min, and the holding time at 1000~1200℃ is 5~10 h.
6. The composite lithium supplement according to claim 1, characterized in that: The preparation method of the Ni@Co@M metal aerogel comprises the following steps: An aqueous solution containing a structure directing agent and a complexing agent, a cobalt source, a nickel source, an M source and a reducing agent are mixed, deoxygenated, heated and stirred at 40-80° C. to form a hydrogel, and dried or solvent replaced to obtain a Ni@Co@M metal aerogel; the M source is a Mo source or a Fe source.
7. The composite lithium supplement according to claim 6, characterized in that: The structure directing agent comprises at least one of a polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, hexadecyltrimethylammonium bromide and a polyoxyethylene polyoxypropylene ether block copolymer; The complexing agent includes at least one of sodium citrate, nitrilotriacetic acid, ethylenediaminetetraacetic acid and adenosine triphosphate; The mass ratio of the structure directing agent to the complexing agent is (40-80): (60-120); In the aqueous solution containing the structure directing agent and the complexing agent, the mass ratio of the total mass of the structure directing agent and the complexing agent to water is 1:(15-25).
8. The composite lithium supplement according to claim 6, characterized in that: The cobalt source includes at least one of cobalt acetate, cobalt acetylacetonate and cobalt nitrate; The nickel source includes nickel acetate and / or nickel nitrate; The Mo source includes molybdenum acetate dimer and / or ammonium molybdate; The Fe source includes ferric nitrate and / or ferric acetylacetonate; The reducing agent includes at least one of dimethylamine borane, sodium borohydride and ascorbic acid.
9. The composite lithium supplement according to claim 6, characterized in that: The mass ratio of the structure directing agent, the complexing agent, the cobalt salt, the nickel salt, the M source and the reducing agent is (40-80):(60-120):(100-150):(100-150):(100-150):(800-1000).
10. The method for preparing the composite lithium supplement according to any one of claims 1 to 9, comprising the following steps: A) Grinding the aqueous solution of lithium oxalate to obtain nano-Li2C2O4; B) The composite and the nano-Li2C2O4 are uniformly dispersed in deionized water, and after ultrasonic treatment, a hydrothermal reaction is performed to obtain a composite lithium supplement.
11. The preparation method according to claim 10, characterized in that: In step B), the mass ratio of the composite to the nano-Li2C2O4 is 1:(3-9); The power of the ultrasonic treatment is 500-3000 W, and the time is 0.5-5 h; The temperature of the hydrothermal reaction is 140-220° C., and the time is 6-24 h.
12. A lithium ion battery, characterized in that: The positive electrode of the lithium-ion battery includes a composite lithium supplement; The composite lithium supplement is the composite lithium supplement according to any one of claims 1 to 9, or is the composite lithium supplement obtained by the preparation method according to any one of claims 10 to 11.
Citation Information
Patent Citations
Lithium supplement composite material and preparation method and application thereof
CN117559013A
Lithium supplement agent and preparation method and application thereof
CN118763219A
Lithium supplement agent and preparation method thereof, positive plate and lithium ion battery
CN118763220A